The embedded GIS technology in LBS - Jiangshui Zhang; Yixin Hua; Tao Feng (2010 18th International Conference on Geoinformatics, 2010)
This paper analyzes the characteristics of the embedded GIS and the LBS. In addition, the paper presents how to solve the key technology in the embedded GIS, such as interactive map matching, keeping high time-effectiveness and using different electronic map modes.